Frequency of Polyhydramnios among Patients with Preterm Delivery at Lady Reading Hospital, Peshawar - Sadaf Jalal, Saima Khattak, Alia Firdus (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The elevated risk of premature delivery should be discussed with polyhydramnios patients. It is advisable to measure the cervical length to evaluate whether or not it is necessary to administer steroids to encourage foetal lung maturity. Patients should also be made aware of the dangers associated with unstable labour necessitating caesarean delivery, umbilical cord prolapse, abruptio placentae, and postpartum haemorrhage. Aim: To determine the frequency of polyhydramnios among patients with preterm delivery presenting to Lady Reading Hospital Peshawar. Study design: Cross-sectional study. Place and duration of study: Department of Obstetrics & Gynaecology, Lady Reading Hospital Peshawar from 1st November 2019 to 25th April 2020. Methodology: One hundred and eighty one women with preterm delivery, gestation age of 24-36 weeks and age between 18-45 years were included. The obstetrical records of these patients were evaluated for the presence of polyhydramnios using AFI they were classified as mild, moderate, and severe polyhydramnios based on AFI. Results: The mean age was 30.39±3.53 years, mean weight of 68.33±7.52 Kg and mean height of 1.59±.0.07 meters, mean BMI 27.07±3.71 kg/m2, mean gestational age 32.30±1.89 weeks and mean AFI was 18.38±6.85 cm. Polyhydramnios was seen in 17.7% of patients. Mild polyhydramnios was 28.1%, moderate 40.6%, and severe was 31.3%. Conclusion: Preterm labour appeared to be influenced more by the underlying aetiology of polyhydramnios than by the relative excess of amniotic fluid as identified by this investigation Keywords: Preterm delivery, Polyhydramnios, Severity